Performance-Based Financing Toolkit - Fritsche, György Bèla; Soeters, Robert; Meessen, Bruno (Washington, DC: World Bank, 2014)
Performance-based financing (PBF) approaches have expanded rapidly in lower-and middle income countries, and especially in Africa. The number of countries has grown from three in 2006 to 32 in 2013. PBF schemes are flourishing and cause considerable demand for technical assistance in executing these health reforms in a rational and accountable manner. Currently there is a lack of knowledge among many health reformers of how to implement performance-based financing pilot projects, and scale them up intelligently. In a context of tremendous demand for solid design and implementation experience and given the rapid expansion of results-based financing (RBF) programs, there is an urgent need to build capacity in designing and implementing PBF programs. As yet there has been little attempt to gather the learning from these experiences together in one volume and, moreover, in a form that serves as a guide to implementers. This toolkit answers the most pressing issues related to the supply-side RBF programs of which PBF forms part.